Preliminary Study of Ultrasonic Welding as a Joining Process for Electrospun Nanofiber Mats - Emilia Wirth (Nanomaterials, 2018)
Electrospinning can be used to create nanofiber mats for diverse applications, from wound dressings and tissue engineering to filters for medical and biotechnological applications. In most of these applications, it is necessary to fix the nanofiber mat on a macroscopic textile fabric, on another nanofiber mat or within a frame to keep it at the desired position. Due to their extremely low thickness and areal mass, however, nanofiber mats are easily destroyed by sewing, and in several situations glued bonds are too thick and not flexible enough. Here we report on ultrasonic welding of polyacrylonitrile nanofiber mats, suggesting this method as a joining process without destruction of the mat morphology for thermoplastic nanofiber mats. A variety of welding patterns results in different adhesion forces between both joined nanofiber mats and different failure mechanisms, with some welding patterns enabling bonding stronger than the mats themselves. Our findings show that ultrasonic welding is a possible joining method for polyacrylonitrile nanofiber mats.